Biofortification of Iodine Concentration in the Leaves of Amaranthus Sp and Ipomea reptan Poir Growing in Hydroponic Culture - Munandar, Munandar; Toumae, Villian; Ammar, Muhammad; Gustiar, Fitra (Seminar Nasional Lahan Suboptimal, 2019)
Munandar M, Toumae V,  Ammar M, Gustiar F.  2019.  Biofortification of Iodine Concentration in the Leaves of Amaranthus Sp and Ipomea reptan Poir Growing in Hydroponic Culture. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 360-369. Palembang: Unsri Press. Biofortification of Amaranthus sp and Ipomea Reptan Poir with iodine is one of the alternative strategies for the enrichment of iodine in vegetable plants. The leafy green vegetables are categorized as horticultural crops, these are easy to cultivate, cheap and affordable for people in rural areas. The aim of this research was to increase iodine concentration in the leaves of Kangkung (Ipomea reptan poir) and spinach (Amaranthus sp) grown in hydroponic culture and evaluate its effect on plant growth. The experiment was conducted from November 2018 to February 2019 at the Hydroponic Shade House, Department of Agronomy, Faculty of Agriculture, Sriwijaya University.The design method used for this research was Completely Randomized Design (CDR) with 4 treatment of Iodine concentration in culture  solution and 4 replications. The treatments were: T0 = 0 ppm, T1 = 25 ppm KI, T2 = 50 ppm KI and T3 = 75 ppm KI, which comprises of 16 experimental units. Each unit of experiment consisted  of a container filled with 6 liters of A&B mix culture solution and    6 plants, i.e. 3 kangkung and 3 spinach were planted. Based on the results, it showed that the analysis of variance for plant height, leaves number, and chlorophyll content were not significantly different for both kangkung and spinach. While the ANOVA for fresh weight of kangkung leaves and stalks were highly significant, and the dry weight of kangkung leaves was significant. The   iodine in leaves   of kangkung (Ipomea reptan poir)   increased with the increasing the amount of iodine concentration supplementation in culture solution. The iodine content in leaves of T1 plant (25ppm) was between the range of 7-15ppm, for T2 plant (50ppm) while  in T3 plant (75 ppm) the iodine content in leaves was between the range of 20-27 ppm. Spinach plant  (Amaranthus sp) grow well only until the Iodine concentration,  treatment of 25 ppm (T1), and the iodine content in leaves reached the range of 7-15ppm. At   the  treatment of 50 ppm KI (T2)  and 75 ppm (T3)  leaves of spinach plants showed  heavy necrosis   as a symptom of  high iodine toxicity, and  plants was dry and died at three weeks after the  Iodine treatment.  In general, it is concluded that  biofortification of Iodine in the leafy green vegetables by applying hydroponic culture is possible.The highest concentration supplementation of Iodine in culture solution  for Iodine biofortification in  Spinach plant  (Amaranthus sp)  was  25 ppm, while for   kangkung (Ipomea reptan poir)  was  50 - 75ppm.Keywords: biofortification, iodine supplementation, hydroponic culture. kangkung, spinach